Eye Signs As Window To The Brain (Case Series) - Manavjot Kaur; Amitoj Singh; RPS Sibia; Vikas Chander; Jasmeen Kaur (GMC Patiala Journal of Research and Medical Education, 2020)
Total ophthalmoplegia is defined as total paralysis of all the muscles of the eye, which in turn results in ptosis, immobility of the eye, dilated non reacting pupil and total loss of accommodation. External ophthalmoplegia refers to the paralysis of extra ocular muscles only. Internal ophthalmoplegia refers to the paralysis of iris and the ciliary muscle.(1) Inter nuclear ophthalmoplegia, a disease which affects the nerves, is a major cause of total ophthalmoplegia . The occurrence of ocular nerve paralysis in a diabetic patient is benign and self limiting and does not involve pupils (2). Retinal migraine is a rare condition that is characterized by repeated attacks of monocular blindness associated with or followed by headache , which may be complicated by irreversible visual loss(3). Informed consent was taken from all 3 patients.Keywords : Total opthalmoplegia , retinal migraine , diabetic mononeuropathy , internuclear opthalmoplegia. We present case series of three patients presenting with opthalmoplegia- each having distinct clinical features having direct bearing on the classical diagnostic patterns of CNS involvement.